Community involvement as a mediating variable: How social media marketing activities affects customer loyalty? - Annisa Yasmin; Arief Helmi; Rita Komaladewi; Irene Deborah; Ariq Zulfahmi Naufal (Jurnal Fokus Manajemen Bisnis, 2024)
The cosmetics industry in Indonesia has great potential, posing great challenges to maintain competitiveness. This research examines community engagement's role as a mediating factor between social media marketing activities and customer loyalty. 194 respondents completed questionnaires to provide study data, which was then analyzed using Smart PLS version 3.0. The findings showed the beneficial effects of social media marketing activities on community engagement and customer loyalty. Furthermore, it has been demonstrated that community engagement increases customer loyalty. However, the results show that community engagement does not mediate between social media marketing activities and customer loyalty. This research highlights the importance of integrating social media into marketing campaigns to foster customer relationships and boost loyalty.